PENINGKATAN KEMAMPUAN KONEKSI MATEMATIS SISWA SMP MELALUI MODEL DISCOVERY LEARNING BERBANTUAN QUIZIZZ - Dianing Anugerah; Darta; Saputra, Jusep (Symmetry: Pasundan Journal of Research in Mathematics Learning and Education, 2023)
Students' mathematical connection skills are still relatively low and still need improvement. To optimize mathematical connections in students, it is necessary to find a solution. One of the alternatives that can be taken by applying the Discovery Learning model. This study aims to determine the increase in mathematical connection skills of students who get the Discovery Learning model assisted by Quizizz higher than students who get conventional learning models, and determine the effectiveness of the Discovery Learning model assisted by Quizizz on mathematical connection skills. The method used in this research is a pseudo-experimental method (quasi) with a non-equivalent control group design research design, the research sample consists of two classes, class VIII H as an experimental class that gets learning with the Discovery Learning model assisted by Quizizz and class VIII G as a control class that gets a conventional learning model. The instrument used in this study is a description of the mathematical connection ability test. The results showed that the increase in mathematical connection skills of students who obtained the Discovery Learning learning model assisted by Quizizz was higher than students who obtained the conventional learning model, and the Discovery Learning model learning assisted by Quizizz was effective on mathematical connection skills. Thus, the Discovery Learning model assisted by Quizizz helps improve and see the effectiveness of students' mathematical connection skills.